Successful sequential therapy for Stenotrophomonas maltophilia infection in a preterm neonate: a case report - Nahari, Majed; Alaboud, Mohammed; Mohinuddin, Syed; Faden, Maheer; Balhareth, Yasser; Alsaleem, Noura (Frontiers in Pediatrics, 2025)
BackgroundA multidrug-resistant pathogen increasingly seen in newborn intensive care units, stenotrophomonas maltophilia presents treatment difficulties for preterm babies.Case presentationA 28-week preterm neonate developed S. maltophilia sepsis following prolonged mechanical ventilation. Initial therapy with trimethoprim- sulfamethoxazole (TMP-SMX) was ineffective, prompting a switch to levofloxacin, which led to clinical recovery and infection clearance.ConclusionThis case highlights the need for tailored antimicrobial strategies in neonatal S. maltophilia infections. Sequential therapy with TMP-SMX and levofloxacin was effective, supporting the judicious use of fluoroquinolones in resistant cases.